Stored platelet number and viscoelastic maximum amplitude are not altered by warming or rapid infusion. Issue 9 (12th July 2019) - Hess, Aaron S.; Ramamoorthy, Jagan; Connor, Joseph; Raife, Thomas; Hess, John R.
Abstract : BACKGROUND: Platelet transfusion is an important aspect of hemostatic resuscitation. Leading textbooks recommend never infusing platelets through warmers or rapid infusers, but there is no evidence to justify this position. MATERIALS AND METHODS: We obtained units of apheresis platelets in plasma from our hospital blood bank and drew a baseline sample from every unit. In the warmer arm, an aliquot from each unit was injected into a fluid warmer heated to 41°C (Ranger, 3M Corporation). After 5 minutes' incubation, the aliquot was withdrawn and sampled. In the infuser arm, we ran the remainder of the unit through a rapid infuser (RI‐2, Belmont Instrument Corporation) at 500 mL/min while warmed, and obtained a sample from the outflow line. A platelet count and viscoelastic maximum amplitude (Haemonetics) was measured from every sample. RESULTS: We observed no clotting or device malfunctions. Average postwarmer temperature was 41.8°C (range, 41.0–43.0). There was no significant difference in postwarmer platelet count or viscoelastic maximum amplitude. Average postinfuser temperature was 37.4°C (range, 36.1–39.0). All units reached the goal infusion rate of 500 mL/min. There was a small increase in postinfuser platelet count. There was no significant change in postinfuser viscoelastic maximum amplitude. CONCLUSION: We were unable to detect any effect of warming or rapid infusion on the number or viscoelastic maximum amplitude of stored apheresis platelets. Contrary to common teaching, these results suggest that rapid infusion and warming does not meaningfully harm apheresis platelets.